2021
DOI: 10.30684/etj.v39i2a.654
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Single Micropile Under Different Lateral Load Rates

Abstract: This paper displays an empirical work of a micropile inserted in the dry river sand with different length to diameter (L/D) ratios (13, 15, 27, 42, and 50). The experimental work is executed on the models of micropile to imitate the side force motion, acting on the micropile head to explain the micropile conduct due to the different side force rates. Forty-five models are tested (eighteen models for short pile, eighteen model for long pile and nine models for intermediate) embedded in different relative densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
3
2
0
Order By: Relevance
“…This behavior may be referred to the fact that the increase in the length of the pile is no longer effective under the same loading and soil conditions so that the thrust of lateral soil resistance against applied lateral loads did not increase at the same rate that occurred between embedment ratios of 20 and 25. This result agreed with findings of [23][24].…”
Section: The Effect Of Embedded Ratio (L/d) On the Load-deflection Curve Of Group Pile (1x2)supporting
confidence: 94%
“…This behavior may be referred to the fact that the increase in the length of the pile is no longer effective under the same loading and soil conditions so that the thrust of lateral soil resistance against applied lateral loads did not increase at the same rate that occurred between embedment ratios of 20 and 25. This result agreed with findings of [23][24].…”
Section: The Effect Of Embedded Ratio (L/d) On the Load-deflection Curve Of Group Pile (1x2)supporting
confidence: 94%
“…Therefore, the group load capacity also increased. This is in agreement with Hazzar et al [2], Rahil et al [3], and Al-Neami et al [13], which reported that the ultimate load increased as the relative density of sand increased.…”
Section: The Influence Of Relative Density Of Sandsupporting
confidence: 92%
“…Increasing cyclic load amplitudes caused the wall's horizontal displacement to increase; this is what was inferred from Figure 9, where all the tests were performed with a frequency of 2 Hz for the cyclic load and (0.5 H) for distances between the railway track and the retaining wall on loose, medium, and dense sand. These results were in accordance with [29,30], where the soil lateral displacement caused by active lateral earth pressure on the wall increases as the dynamic load amplitude does.…”
Section: Effect Of Dynamic Load Amplitudesupporting
confidence: 88%